Degradation of Polycomb Repressive Complex 2 with an EED-Targeted Bivalent Chemical Degrader. Issue 1 (16th January 2020) - Potjewyd, Frances; Turner, Anne-Marie W.; Beri, Joshua; Rectenwald, Justin M.; Norris-Drouin, Jacqueline L.; Cholensky, Stephanie H.; Margolis, David M.; Pearce, Kenneth H.; Herring, Laura E.; James, Lindsey I.
Summary: Protein degradation via the use of bivalent chemical degraders provides an alternative strategy to block protein function and assess the biological roles of putative drug targets. This approach capitalizes on the advantages of small-molecule inhibitors while moving beyond the restrictions of traditional pharmacology. Here, we report a chemical degrader (UNC6852) that targets polycomb repressive complex 2 (PRC2). UNC6852 contains an EED226-derived ligand and a ligand for VHL which bind to the WD40 aromatic cage of EED and CRL2 VHL, respectively, to induce proteasomal degradation of PRC2 components, EED, EZH2, and SUZ12. Degradation of PRC2 with UNC6852 blocks the histone methyltransferase activity of EZH2, decreasing H3K27me3 levels in HeLa cells and diffuse large B cell lymphoma (DLBCL) cells containing EZH2 gain-of-function mutations. UNC6852 degrades both wild-type and mutant EZH2, and additionally displays anti-proliferative effects in this cancer model system. Graphical Abstract: Highlights: Discovery of UNC6852, an EED-targeted bivalent chemical degrader UNC6852 selectively degrades EED, EZH2, and SUZ12 via recruitment of VHL UNC6852 results in loss of PRC2 catalytic activity and decreased H3K27me3 levels UNC6852 is anti-proliferative in DLBCL cell lines with EZH2 activating mutations Abstract : Using an EED-targeted chemical degrader, Potjewyd et al. demonstrate successful degradation of the PRC2 complex. UNC6852 provides a unique tool to study PRC2 function and downregulation of PRC2 activity in cancer and demonstrates the feasibility of developing PRC2-targeted degraders as potential therapeutics.